1982
DOI: 10.1083/jcb.95.2.510
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of cell surface receptors induced by cell-cell contact.

Abstract: Cell surface lectin receptors underwent rapid redistribution after embryonic Xenopus myotomal muscle cells were manipulated into contact in culture. Soybean agglutinin (SBA) receptors became highly concentrated at the contact area and concanavalin A (Con A) and ricin receptors were depleted at the same region. The accumulation of SBA receptors was greatly reduced by the presence of SBA specific sugars in the incubating medium, by precontact binding of SBA to the surface and by lowering the temperature, but it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 14 publications
5
23
0
Order By: Relevance
“…Restriction of sodium channel mobility at neuritic terminals might occur by mechanisms similar to those proposed for the axon hillock region although cell-cell contacts and interactions with extracellular components specific to these regions may also contribute (14,58). The extensive glycosylation of the channel protein, which is required to maintain functional sodium channels in neuroblastoma cells (56), may also be involved in confining channels to specific cellular regions.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction of sodium channel mobility at neuritic terminals might occur by mechanisms similar to those proposed for the axon hillock region although cell-cell contacts and interactions with extracellular components specific to these regions may also contribute (14,58). The extensive glycosylation of the channel protein, which is required to maintain functional sodium channels in neuroblastoma cells (56), may also be involved in confining channels to specific cellular regions.…”
Section: Discussionmentioning
confidence: 99%
“…Migrations of cell surface molecules into specific domains also apparently occurs during flagellar regeneration of Euglena (11) and during sea urchin zygote cleavage (9). It has also been suggested that lateral migrations are responsible for the segregation of surface components during erythrocyte differentiation (6), the spontaneous clustering of low density lipoprotein receptors into coated pits (l) and the accumulation of wheat germ agglutinin receptors into sites of cell-cell contact (2). The redistribution of both PT-1 and PH-20 antigens on the sperm surface resulted from a lateral migration of pre-existing surface molecules in the absence of added ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The arrangement of molecules into discrete domains on the surface of cells is now known to be of widespread occurrence (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Membrane topography may reflect the functional geometry of the cell; for example, in intestinal epithelial cells digestive enzymes are enriched on the apical surface (12).…”
mentioning
confidence: 99%
“…In the early study, it has been shown that the cell-cell interaction induces the redistribution of the cell surface receptors (Chow & Poo, 1982). More recent studies have shown that CAM-mediated contact between pre-and postsynaptic neurons triggers rapid redistribution of both pre-and postsynaptic compartments and promotes synapse formation.…”
Section: Role Of Cams During Development and Synaptogenesismentioning
confidence: 99%